Implementation of a Virtual Private Network by Linux Operation System - Asmaa Al - Sammara (Engineering and Technology Journal, 2005)
Abstract This paper deals with the implementation of a VPN in the Linux Operation System . Linux was found to be a very appealing candidate for such applications for a number of reasons . Firstly the conventional Linux operation system is based on LUNIX , which is renowned for its stability and high performance . Another benefit of Linux operation system is the availability of open source software . Not only is the Linux kernel source code open source but also almost all of the Linux based software is distributed as open source and General Public License ( GPL ) . In this paper , the system is implemented on a prototype of virtual private network that contains five computers .Then the analysis is performed using the result obtained from tests carried out on two VPN protocols and show that IPSec protocols is absolutely more preferable choice of tunneling protocols over openVPN in Linux OS .